(untitled) (Bulletin of criminological association of Ukraine, 2023)
The article is devoted to the theoretical and legal analysis of entrepreneurial activity as an object of administrative-legal regulation. Special attention is paid to the main problems of the development of entrepreneurial activity under martial law and economic crisis. A definition of the concept of "entrepreneurial activity" is proposed, and the key features of such activity are listed. The opinion is substantiated that entrepreneurial activity is controlled and regulated by the state using an administrative-legal mechanism. The author’s definition of the concept of "administrative-legal regulation of entrepreneurial activity" is proposed. The main tasks of administrative-legal regulation of entrepreneurial activity are determined, in particular: ensuring administrative- legal protection of entrepreneurial activity; implementation of administrative control and supervision over compliance with legislation in the specified area; ensuring compliance with fair competition; compliance with the administrative procedure in the field of state registration of legal entities and individual entrepreneurs, etc. The main instruments of administrative and legal influence on entrepreneurial activity are characterized, such as: technical regulation; state registration of business entities; licensing, standardization, certification; granting of permits, patents, quotas; state economic support for business entities, etc. The thesis is substantiated that entrepreneurial activity is an object of influence of administrative law norms. It is stated that entrepreneurial activity is a complex, multifaceted object of administrative and legal regulation. It is found out that thanks to special administrative instruments, the state ensures compliance with the law, protects public interests and creates conditions for sustainable business development. It is summarized that entrepreneurial activity, as an object of administrative and legal regulation, is characterized by a combination of economic freedom and administrative and legal supervision and control. The article identifies the main characteristic features of entrepreneurial activity, as an object of administrative and legal regulation.